2017
DOI: 10.1016/j.oraloncology.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of tobacco/nut chewing HPV-negative early stage tongue tumors identify MMP10 as a candidate to predict metastases

Abstract: HighlightsPortrait of somatic alterations in HPV-negative early stage tongue tumors with tobacco signature.Upregulation of genes related to EMT pathway identified by transcriptome analysis.MMP10 could be a candidate prognostic biomarker to stratify patients who develop metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 53 publications
6
32
0
Order By: Relevance
“…Reported mutation burden in oral squamous cell carcinoma is between 2 and 12 mutations per MB. 10,11 We observed 10 mutations per MB in cells treated with shisha extract with similar mutation spectrum as reported in whole-exome sequence analysis study of 15 OSCC patients with history of Shamma exposure. 25 In addition, missense variant(s) were identified in SAM and SH3 domain containing 1 (SASH1), Filamin C (FLNC), and Adenylate Cyclase 8 (ADCY8) with >30% allele frequency supported by at least 10 reads and predicted to be deleterious by ≥3…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Reported mutation burden in oral squamous cell carcinoma is between 2 and 12 mutations per MB. 10,11 We observed 10 mutations per MB in cells treated with shisha extract with similar mutation spectrum as reported in whole-exome sequence analysis study of 15 OSCC patients with history of Shamma exposure. 25 In addition, missense variant(s) were identified in SAM and SH3 domain containing 1 (SASH1), Filamin C (FLNC), and Adenylate Cyclase 8 (ADCY8) with >30% allele frequency supported by at least 10 reads and predicted to be deleterious by ≥3…”
Section: Discussionsupporting
confidence: 81%
“…8 A comparative study on exposure to tobacco-specific nitrosamines (NNAL) in shisha smokers, cigarette smokers, and non-smokers has shown that regular shisha smokers are exposed to about 5-10 times greater quantities of nitrosamines than non-smokers which is equivalent to pack-a-day cigarette smokers. 9 Risk associations and pathogenesis of oral cancer is well documented 10,11 ; however, it is not extensively studied in shisha smokers. We developed a cell line model using immortalized normal oral keratinocytes by chronically treating them with shisha extract for a period of 8 months.…”
mentioning
confidence: 99%
“…Interestingly, MMP10 and MMP13 are both members of matrix metalloproteinase family and promote cell invasion and metastases. A previous study indicated that MMP10 might be a potential prognostic biomarker for oral cancer metastases . GDF15, another validated candidate gene downstream of LINC01133, belongs to the TGF‐β superfamily.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study indicated that MMP10 might be a potential prognostic biomarker for oral cancer metastases. 24 GDF15, another validated candidate gene downstream of LINC01133, belongs to the TGF-β superfamily. Multiple studies have demonstrated that GDF15 and other TGF-β superfamily members promote metastases of malignant tumors, including OSCC.…”
Section: Transcriptome Expression Analysis Viamentioning
confidence: 99%
“…It is widely accepted that HNSCC occurs as a result of cumulative genetic/epigenetic abnormalities in cancer-associated genes. However, to date, a limited number of genes have been reported as candidate somatic drivers for HNSCC, including tumor protein p53 (19), Akt1, APC, CCND1, fibroblast growth factor receptor 3 (FGFR3), NOTCH1, phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha (PI3KCA), and phosphatase and tensin homolog (PTEN) (20)(21)(22)(23)(24). In addition, the HNSCC-specific cancer-associated genes/pathways are not well illustrated.…”
Section: Discussionmentioning
confidence: 99%